Physiological Levels of Nitric Oxide Diminish Mitochondrial Superoxide. Potential Role of Mitochondrial Dinitrosyl Iron Complexes and Nitrosothiols - Dikalov, Sergey I.; Mayorov, Vladimir I.; Panov, Alexander V. (Frontiers in Physiology, 2017)
Mitochondria are the major source of superoxide radicals and superoxide overproduction contributes to cardiovascular diseases and metabolic disorders. Endothelial dysfunction and diminished nitric oxide levels are early steps in the development of these pathological conditions. It is known that physiological production of nitric oxide reduces oxidative stress and inflammation, however, the precise mechanism of “antioxidant” effect of nitric oxide is not clear. In this work we tested the hypothesis that physiological levels of nitric oxide diminish mitochondrial superoxide production without inhibition of mitochondrial respiration. In order to test this hypothesis we analyzed effect of low physiological fluxes of nitric oxide (20 nM/min) on superoxide and hydrogen peroxide production by ESR spin probes and Amplex Red in isolated rat brain mitochondria. Indeed, low levels of nitric oxide substantially attenuated both basal and antimycin A-stimulated production of reactive oxygen species in the presence of succinate or glutamate/malate as mitochondrial substrates. Furthermore, slow releasing NO donor DPTA-NONOate (100 µM) did not change oxygen consumption in State 4 and State 3. However, the NO-donor strongly inhibited oxygen consumption in the presence of uncoupling agent CCCP, which is likely associated with inhibition of the over-reduced complex IV in uncoupled mitochondria. We have examined accumulation of dinitrosyl iron complexes and nitrosothiols in mitochondria treated with fast-releasing NO donor MAHMA NONOate (10 µM) for 30 minutes until complete release of NO. Following treatment with NO donor, mitochondria were frozen for direct detection of dinitrosyl iron complexes using Electron Spin Resonance (ESR) while accumulation of nitrosothiols was measured by ferrous-N-Methyl-D-glucamine dithiocarbamate complex, Fe(MGD)2, in lysed mitochondria. Treatment of mitochondria with NO-donor gave rise to ESR signal of dinitrosyl iron complexes while ESR spectra of Fe(MGD)2 supplemented mitochondrial lysates showed presence of both dinitrosyl iron complexes and nitrosothiols. We suggest that nitric oxide attenuates production of mitochondrial superoxide by posttranslational modifications by nitrosylation of protein cysteine residues and formation of protein dinitrosyl iron complexes with thiol-containing ligands and, therefore, nitric oxide reduction in pathological conditions associated with endothelial dysfunction may increase mitochondrial oxidative stress.